Physical, Emotional, Medical, and Socioeconomic Status of Patients With NMOSD: A Cross-Sectional Survey of 123 Cases From a Single Center in North China - Jia, Zhen; Dong, XiuYu; Song, Shuang; Guo, Ruoyi; Zhang, Lu; Liu, Jia; Li, Bin (Frontiers in Neurology, 2021)
Objective: This study aimed to assess the physical, emotional, medical, and socioeconomic conditions of patients with neuromyelitis optica spectrum disorder (NMOSD) in North China. Methods: A cross-sectional survey of patients with NMOSD was performed, based on an established questionnaire from the Multiple Sclerosis Patient Survival Report 2018. Logistic regression analysis was conducted to define the significant determinants of certain physical or emotional characteristics of patients. A total of 123 patients were included. Results: A total of 63.4% of participants were initially diagnosed with conditions other than NMOSD, with a median delay of six months for accurate diagnosis. An aggregate of 72.2% of patients had one or more relapses, corresponding to an annual relapse rate of 0.8. Paresthesia was the most frequent physical symptom among patients both at disease onset (53.7%) and throughout the duration of the disease (86.2%). Onset in elderly (>50 years) patients was associated with an annual Expanded Disability Status Scale increase ≥1, compared with onset in younger (<30 years) patients (P = 0.001, OR = 7.83). A total of 76.4% of patients had received attack-prevention treatments in the remission phase, and 31.7% and 10.6% of patients had ever been administered rituximab and traditional Chinese medicine, respectively. Additionally, 63.4% and 43.1% of patients reported participating in few or no social activities and being out of work because of the disease. To be noted, 76.4% of patients reported suffering from negative emotions, with the most frequent being worry (60.2%), with 20.3% of patients experiencing suicidal thoughts. The inability to work and participating in few or no social activities due to NMOSD were two determinants of experiencing negative emotions (Pwork = 0.03, ORwork = 3.34; Psocial activities = 0.02, ORsocial activities = 3.19). Conclusion: This study reported patient perspectives on NMOSD in North China, whereby demonstrating that the inability to work and participating in few or no social activities due to NMOSD rather than the physical impairment caused by the disease, was directly associated with patients experiencing negative emotions. This insight offers potential ways to manage patients’ negative emotions by enhancing family and social support and facilitating active employment.